Supporting Patron Access to Rural Libraries in Maine through the Balsam Library Consortium - Grant, Nancy (Maine Policy Review, 2024)
Maine Balsam Library Consortium supports Maine's isolated rural libraries with inexpensive access to the Open Source Evergreen automated card catalog. Rural libraries deal with limited budges, limited library training or experience, and minimal technology support. The Balsam Consortium provides an inexpensive automated card catalog, along ongoing technology support, and a mentorship approach to meeting the needs of each local library.